European S2k guideline on chronic pruritus: in cooperation with the European Dermatology Forum (EDF) - Weisshaar, Elke; Müller, Simon; Szepietowski, Jacek C.; Dalgard, Florence; Garcovich, Simone; Kupfer, Jörg; Gimenez-Arnau, Ana; Lambert, Julien; Mettang, Thomas; Misery, Laurent; Savk, Ekin; Tschachler, Erwin; et al. (Acta dermato-venereologica, 2025)
Pruritus is a frequent symptom in medicine. Population-based studies show that one in five persons in the general population has suffered from chronic pruritus (CP) at least once in their lifetime, with a 12-month incidence of 7%. CP, which can affect all age groups, is associated with numerous, often interdisciplinary medical conditions. It needs a precise diagnostic work-up to identify causes and relevant comorbidities. Management of CP comprises treatment of the underlying disease as well as topical and systemic therapies. Treating CP needs to be targeted, multimodal and performed in a step-wise procedure requiring an interdisciplinary approach. In recent years, novel on-label therapies have been approved for CP, including therapies for chronic prurigo and cholestatic pruritus. We present the updated European guideline on chronic pruritus by a team of European pruritus experts from different disciplines.
Gesehen am 03.02.2026